The Role Of Personal Brand Orientation And Brand Orchestration In Social Commerce (Journal of Pharmaceutical Negative Results, 2023)
SME growth on social commerce is on the rise. Founders invest substantial time and effort in gaining social media recognition, yet it is unclear what benefits they receive from this investment. The purpose of this study is to investigate the impact of Personal Brand Orientation (PBO) on SME Digital Firm Performance in an Indonesian Online Social Commerce. This study hypothesizes that all PBO dimensions are positively associated with SME Digital Firm Performance, and that networking capabilities and brand orchestration aid to moderate PBO's effect. The study employed a quantitative method and partial least square structural equation modeling technique in data processing and interpretation due to its applicability for predictive research models. 504 sample data were collected from SME staff employees via online surveys performed in Indonesia between September and October 2021. This research examines how founder personal branding can be leveraged as a strategic resource for SMEs. Furthermore, an assessment of SMEs' capabilities provides a more complete picture, allowing for a more in-depth understanding of the founder's marketing appeal. To test given study hypotheses, partial least square structural equation modeling (PLS-SEM) was applied. This study's use of upper echelon theory later confirmed the favorable association between founder vision and founder-relevant education for personal brand orientation. This study, on the other hand, showed a substantial relationship between personal brand orientation and digital firm performance, which was significantly mediated by networking skills.